2007
DOI: 10.1038/modpathol.3800823
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the urinary tract: a clinicopathological study of 30 pure and mixed cases

Abstract: We studied 28 cases of lymphoepithelioma-like carcinoma of the bladder, one case in the renal pelvis, and one in the urethra. The mean age of the patients was 67.6 years with 21 (70%) males. Seventeen cases (56.7%) were pure with the remaining mixed with other patterns of carcinoma, including invasive urothelial carcinoma (n ¼ 10), invasive adenocarcinoma (n ¼ 3), and squamous cell carcinoma (n ¼ 2). The surface demonstrated carcinoma in situ (CIS) in six cases, noninvasive high-grade papillary urothelial carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
141
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 21 publications
(54 reference statements)
2
141
0
2
Order By: Relevance
“…Since then there have been only a few relatively small studies on LELC of urinary bladder 28. The largest study was reported by Tamas et al8 who described 17 pure 13 mixed LELC. Prior to that Lopez-Beltran et al5 reported 3 pure, 6 predominant and 4 focal LELCs of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then there have been only a few relatively small studies on LELC of urinary bladder 28. The largest study was reported by Tamas et al8 who described 17 pure 13 mixed LELC. Prior to that Lopez-Beltran et al5 reported 3 pure, 6 predominant and 4 focal LELCs of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is frequently associated with lymphoepithelioma of the nasopharynx and LELC arising in the lung, stomach, thymus and salivary gland 1289. However, such an association has not been documented for LELC of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations